Communication network requirements for major smart grid applications in HAN, NAN and WAN - Kuzlu, Murat; Pipattanasomporn, Manisa; Rahman, Saifur (Computer networks (Amsterdam, Netherlands : 1999), 2014)
Since the introduction of the smart grid, accelerated deployment of various smart grid technologies and applications have been experienced. This allows the traditional power grid to become more reliable, resilient, and efficient. Despite such a widespread deployment, it is still not clear which communication technology solutions are the best fit to support grid applications. This is because different smart grid applications have different network requirements – in terms of data payloads, sampling rates, latency and reliability. Based on a variety of smart grid use cases and selected standards, this paper compiles information about different communication network requirements for different smart grid applications, ranging from those used in a Home Area Network (HAN), Neighborhood Area Network (NAN) and Wide-Area Network (WAN). Communication technologies used to support implementation of selected smart grid projects are also discussed. This paper is expected to serve as a comprehensive database of technology requirements and best practices for use by communication engineers when designing a smart grid network.